Pentingnya Gizi Seimbang pada Siswa di SMA Negeri 87 Jakarta - Adhila Fayasari; Sandra Sandra; Mutiah Mustaqimatusy Syahadah; Dewi Wulandari; Rizka Akbar (Kolaborasi: Jurnal Pengabdian Masyarakat, 2023)
Introduction: The nutritional status of adolescents is influenced by several factors, including food intake, lifestyle, physical activity, and knowledge. The nutritional status of adolescents at SMA Negeri 87 Jakarta is still problematic, and based on observations, several behaviors are found that are still not in accordance with balanced nutrition. Objective: The purpose of this activity is to increase students' knowledge and awareness about balanced nutrition at 87 Highschool, Jakarta. Method: This public service was conducted by the Binawan University team, consisting of lecturers and students in 87 Highschool, Jakarta. This activity is carried out using an online method for 3 meetings from December 2021 – January 2022. The topics given are adolescent health during the COVID-19 pandemic, hoaxes about the COVID-19 vaccine, concepts and principles of balanced nutrition, consumption of vegetables and fruit, breakfast. health, physical activity, and weight control. Evaluation was carried out by giving pretest and posttest to determine the knowledge of participants after being given counseling. Result: This pubic service activity went smoothly and all activities were carried out. Based on the evaluation, the participants' interest was high and there was an increase in knowledge after being given education, except for topic 1 which was related to the Covid19 vaccine. The problem with low participation is because it coincides with student activities, so there are some students who are not present in the entire pubic service series. Conclusion: Providing regular and comprehensive counseling can increase students' knowledge about balanced nutrition and is expected to increase awareness of balanced nutrition behavior in the future.